Micro-nano dual-scale hard alloy and preparation method thereof
Through the combination of multi-spray additive manufacturing equipment and vacuum sintering, micro-nano double-scale cemented carbide with high hardness and high toughness is prepared, solving the problems of complexity and high cost in traditional processes, and achieving accurate control of the structure and improving performance.
Patent Information
- Application Number
- CN202411935268.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to simultaneously improve the strength and toughness of cemented carbides. The traditional preparation process is complex, the cost is high, and the micro-nano double-scale structure is not easy to control.
Using a combination of multi-spray additive manufacturing equipment and vacuum sintering, a three-dimensional model of a two-scale structure is designed through software, and a mixed slurry of micro-scale WC and nano-scale WC are sprayed with different nozzles, and powder is spread layer by layer to form alternately distributed micro-scale WC and nano-scale WC grains, and then vacuum sintering is carried out.
The uniformity and grain size distribution of micro-nano biscale structures are effectively controlled, the production process is simplified, the production cost is reduced, and the hardness and toughness of cemented carbide is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide manufacturing, and in particular relates to a micro-nano dual-scale cemented carbide. Background Art
[0002] Cemented carbide is an alloy material prepared by powder sintering method with refractory metal compounds (WC, TiC, TaC, NbC, etc.) as hard phase and transition metals (Fe, Co, Ni) as bonding phase. Cemented carbide has the advantages of high strength and hardness, good wear resistance, etc. It is mainly used to make cutting tools and is widely used in the field of cutting. In recent years, with the development of materials science and high-speed cutting, higher requirements have been put forward for the strength, hardness, wear resistance and toughness of cemented carbide tools. At present, in order to improve strength and hardness, researchers mainly prepare ultrafine grains or nanocrystalline cemented carbides by refining grains, but the toughness is low. In order to improve toughness, by adding more bonding phases or preparing cemented carbide with micron-sized grains, the hardness and wear resistance of cemented carbide will be reduced. Therefore, it is necessary to develop a new cemented carbide tool material that can improve strength and toughness at the same time.
[0003] Micro-nano dual-scale cemented carbide has two scales of WC grain structure. The nano-scale WC grains have high strength and hardness, which increases the wear resistance; the micron-scale WC grains have good toughness, which increases the ability to resist crack propagation. The two scales of WC grains are evenly distributed, which can make the cemented carbide have higher toughness while maintaining high hardness, thereby increasing the service life of the cemented carbide. At present, the preparation of micro-nano dual-scale cemented carbide mainly uses WC powder raw materials of different particle sizes, which are pressed into shape after ball milling, and then sintered to obtain a micro-nano dual-scale structure. The pressing process has high requirements, and the sintering process is relatively complicated. In addition, the size of the dual-scale WC grains is not easy to control, which makes the alloy cost high. Therefore, a new method for preparing micro-nano dual-scale cemented carbide has been developed to accurately control the distribution of micron-scale WC and nano-scale WC grains and the size of micro-nano dual-scale grains, give full play to the high toughness of micron-scale WC grains to inhibit crack propagation, and the high hardness of nano-scale WC grains to increase wear resistance, thereby improving the mechanical properties of the alloy such as hardness and toughness, and meeting the requirements of some specific fields for cemented carbide with both high toughness and high hardness. This is of great significance for the application of micro-nano dual-scale cemented carbide and is the future development trend of cemented carbide.
[0004] At present, additive manufacturing technology mainly adopts the method of selective electron beam or laser melting, with electron beam or laser as the heating source, scanning layer by layer on the powder bed according to the path planned in the slicing model, so that the cemented carbide powder undergoes a certain degree of melting and solidification. It has the advantages of rapid prototyping and controllable shape and structure, and is used in many material preparation processes.
[0005] In summary, for cemented carbide that requires high hardness and high toughness, nano-scale WC grains are formed inside the alloy to keep the alloy at a high hardness and wear resistance. At the same time, micron-scale WC grains are distributed around the nano-scale WC powder to hinder crack propagation, thereby improving the toughness of the alloy. The microstructure of nano-scale WC grains uniformly distributed around the micron-scale WC grains can make the alloy obtain high hardness while maintaining high toughness. Therefore, using additive manufacturing technology to print mixed powders of different powder sizes into the required micro-nano dual-scale structure of cemented carbide blanks, and then preparing cemented carbide with micro-nano dual-scale structure through vacuum sintering can significantly reduce the production cost of micro-nano dual-scale structure cemented carbide. For example, patent publication number CN117684035A discloses a nanocrystalline cemented carbide additive manufacturing method, which uses ultrafine polycrystalline WC powder, Co powder, and grain growth inhibitor as raw materials, prepares a uniformly dispersed mixed powder by ball milling, and then prepares a printing feed with a binder in a vacuum mixer-granulator, and then uses fused deposition molding to print and form a cemented carbide green body in an inert gas environment, and finally degreases the green body + two-step sintering to prepare a nano cemented carbide. For example, patent publication number CN112391556A discloses a high-strength and high-conductivity Cu-Cr-Nb alloy with a double-peak grain size and double-scale nanophase reinforcement. Through selective laser melting and special heat treatment process, a high-performance Cu-Cr-Nb alloy with a double-peak grain size and double-scale nanophase reinforcement is prepared. Both of the above patents are prepared by additive manufacturing process by blending double-scale alloy powders, but there are technical problems that the micro-nano double-scale structure is difficult to control and the grain size is difficult to control. Summary of the invention
[0006] In response to the above technical problems, the present invention proposes a micro-nano dual-scale cemented carbide and a preparation method thereof. The invention is suitable for the processing and manufacturing of micro-nano dual-scale structured cemented carbide with high requirements for high hardness and high toughness. The structure of the micro-nano dual-scale cemented carbide can be controlled at any time through additive manufacturing molding technology, thereby shortening the manufacturing cycle and saving materials, and is suitable for mass manufacturing.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A method for preparing a micro-nano dual-scale cemented carbide comprises the following steps:
[0009] (1) mixing micron-sized WC and binder phase I and wet grinding them to obtain a micron-sized WC mixed slurry;
[0010] (2) mixing and wet-grinding the nano-scale WC and the binder phase II to obtain a nano-scale WC mixed slurry;
[0011] (3) Then, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are placed in an additive manufacturing device and sprayed out through different nozzles, and a three-dimensional model of the dual-scale structure is designed by software, and then the additive manufacturing device is controlled by a computer to print and form according to a program to obtain a cemented carbide blank; during the printing and forming process, the multiple nozzles of the additive manufacturing device spread the powder and melt and deposit it layer by layer from bottom to top, and the slurry in each layer is deposited line by line to cover the entire layer;
[0012] (4) Vacuum sintering the cemented carbide blank to obtain a micro-nano dual-scale structure cemented carbide
[0013] The micron-scale WC particle size is 0.8-5 μm; the nano-scale WC particle size is 0.1-0.5 μm.
[0014] The bonding phase I and the bonding phase II are both Co powders, and the particle size of the Co powder is 0.6-1.0 μm.
[0015] The ratio of micron-grade WC to bonding phase I is 70-94wt% for micron-grade WC and 6-30wt% for bonding phase I, and the sum of the two is 100%; the ratio of nano-grade WC to bonding phase II is 70-94wt% for nano-grade WC and 6-30wt% for bonding phase II, and the sum of the two is 100%.
[0016] The wet grinding method in steps (1) and (2) is as follows: adding a molding agent at a ratio of 1-60% of the total weight of the ingredients, adding a wet grinding agent at a ratio of 1-60% of the total weight of the ingredients, the ball-to-material ratio is (6-12):1, the rotation speed is 50-500 r / min, and the time is 6-60 h.
[0017] The molding agent is polyethylene glycol or paraffin, and the wet grinding agent is ethanol.
[0018] The three-dimensional model of the dual-scale structure in step (3) is that the micron phase and the nano phase are alternately distributed in each layer, and the corresponding layer-by-layer powder spreading method is: in each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are alternately deposited to form alternatingly distributed micron-scale WC mixed slurry strips and nano-scale WC mixed slurry strips.
[0019] The three-dimensional model of the dual-scale structure in step (3) is a layer of micron phase and a layer of nano phase alternately distributed, and the corresponding layer-by-layer powder spreading method is: first deposit a layer of micron-scale WC mixed slurry, and then deposit a layer of nano-scale WC mixed slurry, and the micron-scale WC mixed slurry layer and the nano-scale WC mixed slurry layer are deposited alternately.
[0020] The vacuum sintering conditions are: vacuum degree 10-2-10-4Pa, 300-800°C, heat preservation for 1-3h for degreasing, then continue to heat up to 1300-1500°C, and keep warm for 0.2-4h.
[0021] A micro-nano dual-scale cemented carbide comprises 70-94wt% of hard phase micron-scale WC and nano-scale WC, and 6-30wt% of bonding phase; the mass ratio of the micron-scale WC and the nano-scale WC is (3-7): (3-7).
[0022] Beneficial effects of the invention: The invention adopts a combination of multi-nozzle additive manufacturing equipment and vacuum sintering to prepare micro-nano dual-scale structured cemented carbide, which effectively solves the shortcomings of the traditional preparation process of micro-nano dual-scale cemented carbide, such as complex molding process, uneven powder particle size distribution, and difficult control of micro-nano dual-scale grain size after sintering, complex process, difficult control of product microstructure, and high production cost. It also indirectly shortens the preparation cycle and solves the problem of difficult grasp of blanking technology for parts with complex shapes and structures.
[0023] The method of the present invention includes four steps of raw material configuration, ball milling, molding and sintering. The molding step is to put the slurry into the additive manufacturing equipment, program it according to the required micro-nano dual-scale structure requirements, and then control the additive manufacturing equipment to print and mold it through a computer to obtain the required micro-nano dual-scale structure cemented carbide blank, and then vacuum sinter it to obtain a micro-nano dual-scale cemented carbide with uniform grain size distribution. Compared with the traditional preparation method, the uniformity and grain size of the micro-nano dual-scale structure can be effectively controlled, and the production process is simplified, reducing the production cost.
[0024] Traditional manufacturing technology requires drying, sieving and pressing after ball milling, while additive manufacturing technology can obtain instructions directly from design documents to handle the same complex processes mentioned above. More importantly, additive manufacturing technology requires less operating skills and mechanical equipment, and can use one device to complete multiple processes required for traditional mechanical manufacturing. It can also provide people with new production methods in remote environments or extreme situations. Additive manufacturing technology produces fewer by-products during the manufacturing process, which can greatly reduce the excessive use and waste of raw materials and improve enterprises' awareness of energy conservation and emission reduction.
[0025] The distribution and content of micro-nano WC grains in the micro-nano dual-scale structure cemented carbide prepared by the present invention can be controlled by additive manufacturing technology, which can improve the overall performance of the cemented carbide. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A method for preparing a micro-nano dual-scale cemented carbide comprises the following steps:
[0029] (1) Mix 86 g of WC powder with a particle size of 1.0 μm and 14 g of Co powder with a particle size of 0.8 μm;
[0030] (2) 86 g of WC with a particle size of 0.3 μm and 14 g of Co powder with a particle size of 0.8 μm were mixed;
[0031] (3) The above two raw materials were added to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 8:1, and 50% (volume fraction) PEG binder and 50% (volume fraction) ethanol were added for wet grinding at a speed of 400 r / min and a wet grinding time of 48 h to obtain a micron-scale WC mixed slurry and a nano-scale WC mixed slurry;
[0032] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.1 mm, the laser power was 400 W, the preheating temperature was 400 ° C, the thickness of each layer of powder was 0.03 mm, and the scanning speed was 2.0 mm / s.
[0033] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised from below Pa to 750°C and kept at this temperature for 4.0 hours for degreasing, and then continued to be raised to 1400°C and kept at this temperature for 3 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0034] Example 2
[0035] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0036] (1) Mix 86 g of WC powder with a particle size of 3.0 μm and 14 g of Co powder with a particle size of 1.0 μm;
[0037] (2) 86 g of WC with a particle size of 0.5 μm and 14 g of Co powder with a particle size of 1.0 μm were mixed;
[0038] (3) The above two raw materials were respectively added to a wet ball mill for wet grinding, with a ball-to-material ratio of 10:1, and 20% (volume fraction) PEG binder and 40% (volume fraction) ethanol were added for wet grinding at a speed of 200 r / min and a wet grinding time of 72 h to obtain a micron-scale WC mixed slurry and a nano-scale WC mixed slurry;
[0039] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.2 mm, the laser power was 300 W, the preheating temperature was 300 ° C, the thickness of each layer of powder was 0.02 mm, and the scanning speed was 1.5 mm / s.
[0040] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised to 750°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1450°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0041] Example 3
[0042] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0043] (1) Mix 86 g of WC powder with a particle size of 5.0 μm and 14 g of Co powder with a particle size of 0.8 μm;
[0044] (2) 86 g of WC with a particle size of 0.4 μm and 14 g of Co powder with a particle size of 1.0 μm were mixed;
[0045] (3) adding the above two raw materials to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 12:1, adding 50% (volume fraction) PEG binder and 50% (volume fraction) ethanol for wet grinding, the speed is 300 r / min, the wet grinding time is 60 h, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are obtained;
[0046] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.2 mm, the laser power was 500 W, the preheating temperature was 200 ° C, the thickness of each layer of powder was 0.01 mm, and the scanning speed was 1.0 mm / s.
[0047] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised to 750°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1480°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0048] Example 4
[0049] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0050] (1) Mix 94 g of WC powder with a particle size of 5.0 μm and 6 g of Co powder with a particle size of 0.8 μm;
[0051] (2) 86 g of WC with a particle size of 0.4 μm and 14 g of Co powder with a particle size of 1.0 μm were mixed;
[0052] (3) The above two raw materials were respectively added to a wet ball mill for wet grinding, with a ball-to-material ratio of 10:1, and 60% (volume fraction) PEG binder and 60% (volume fraction) ethanol were added for wet grinding at a speed of 500 r / min and a wet grinding time of 20 h to obtain a micron-scale WC mixed slurry and a nano-scale WC mixed slurry;
[0053] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.2 mm, the laser power was 500 W, the preheating temperature was 200 ° C, the thickness of each layer of powder was 0.01 mm, and the scanning speed was 1.0 mm / s.
[0054] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -3The temperature was raised from below Pa to 800°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1500°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0055] Example 5
[0056] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0057] (1) Mix 70 g of WC powder with a particle size of 0.8 μm and 30 g of Co powder with a particle size of 1.0 μm;
[0058] (2) Mix 70 g of WC with a particle size of 0.1 μm and 30 g of Co powder with a particle size of 1.0 μm;
[0059] (3) adding the above two raw materials to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 6:1, adding 10% (volume fraction) PEG binder and 10% (volume fraction) ethanol, and then wet grinding, the speed is 50r / min, the wet grinding time is 60h, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are obtained;
[0060] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.2 mm, the laser power was 500 W, the preheating temperature was 200 ° C, the thickness of each layer of powder was 0.01 mm, and the scanning speed was 1.0 mm / s.
[0061] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -2 The temperature was raised from below Pa to 300°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1300°C and kept at this temperature for 4 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0062] Example 6
[0063] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0064] (1) Mix 90 g of WC powder with a particle size of 1.8 μm and 10 g of Co powder with a particle size of 0.8 μm;
[0065] (2) Mix 70 g of WC powder with a particle size of 0.3 μm and 30 g of Co powder with a particle size of 1.0 μm;
[0066] (3) adding the above two raw materials to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 12:1, adding 50% (volume fraction) PEG binder and 50% (volume fraction) ethanol for wet grinding, the speed is 300 r / min, the wet grinding time is 60 h, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are obtained;
[0067] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. In each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were deposited alternately. From the cross-section, the two slurries were distributed in a checkerboard pattern. The nozzle diameter of the additive manufacturing equipment used was 0.2 mm, the laser power was 500 W, the preheating temperature was 200 ° C, the thickness of each layer of powder was 0.01 mm, and the scanning speed was 1.0 mm / s.
[0068] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised to 750°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1480°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0069] Example 7
[0070] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0071] (1) Mix 86 g of WC powder with a particle size of 5.0 μm and 14 g of Co powder with a particle size of 0.8 μm;
[0072] (2) 86 g of WC with a particle size of 0.4 μm and 14 g of Co powder with a particle size of 1.0 μm were mixed;
[0073] (3) adding the above two raw materials to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 12:1, adding 50% (volume fraction) PEG binder and 50% (volume fraction) ethanol for wet grinding, the speed is 300 r / min, the wet grinding time is 60 h, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are obtained;
[0074] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. First, a layer of micron-scale WC mixed slurry was deposited, and then a layer of nano-scale WC mixed slurry was deposited. The two were deposited alternately. From the cross-section, the two slurries were distributed alternately layer by layer. The nozzle diameter of the additive manufacturing equipment used was 0.2mm, the laser power was 500W, the preheating temperature was 200℃, the thickness of each layer of powder was 0.01mm, and the scanning speed was 1.0mm / s.
[0075] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised to 750°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1480°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0076] Example 8
[0077] A method for preparing a micro-nano dual-scale cemented carbide, characterized in that it comprises the following steps:
[0078] (1) Mix 80 g of WC powder with a particle size of 3.0 μm and 20 g of Co powder with a particle size of 0.6 μm;
[0079] (2) Mix 80 g of WC powder with a particle size of 0.3 μm and 20 g of Co powder with a particle size of 0.6 μm;
[0080] (3) adding the above two raw materials to a wet ball mill for wet grinding, respectively, with a ball-to-material ratio of 12:1, adding 50% (volume fraction) PEG binder and 50% (volume fraction) ethanol for wet grinding, the speed is 300 r / min, the wet grinding time is 60 h, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are obtained;
[0081] (4) The three-dimensional model of the dual-scale structure was designed by software, and the micron-scale WC mixed slurry and the nano-scale WC mixed slurry were placed in different barrels of the additive manufacturing equipment. The slurry extrusion speed was controlled by the program, and the laser rapid scanning solidification molding was used at the same time, and the powder was melted and deposited layer by layer from bottom to top. First, a layer of micron-scale WC mixed slurry was deposited, and then a layer of nano-scale WC mixed slurry was deposited. The two were deposited alternately. From the cross-section, the two slurries were distributed alternately layer by layer. The nozzle diameter of the additive manufacturing equipment used was 0.2mm, the laser power was 500W, the preheating temperature was 200℃, the thickness of each layer of powder was 0.01mm, and the scanning speed was 1.0mm / s.
[0082] (5) Place the blank in a vacuum sintering furnace and evacuate the vacuum furnace to 10 -4 The temperature was raised to 750°C and kept at this temperature for 3.0 hours for degreasing, and then continued to be raised to 1480°C and kept at this temperature for 2 hours for sintering. After the holding period, the furnace was cooled to room temperature to obtain a micro-nano dual-scale structure cemented carbide.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing micro-nano dual-scale cemented carbide, characterized in that: The following steps are involved: (1) mixing micron-sized WC and binder phase I and wet grinding them to obtain a micron-sized WC mixed slurry; (2) mixing and wet-grinding the nano-scale WC and the binder phase II to obtain a nano-scale WC mixed slurry; (3) Then, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are placed in an additive manufacturing device and sprayed out through different nozzles, and a three-dimensional model of the dual-scale structure is designed by software, and then the additive manufacturing device is controlled by a computer to print and form according to a program to obtain a cemented carbide blank; during the printing and forming process, the multiple nozzles of the additive manufacturing device spread the powder and melt and deposit it layer by layer from bottom to top, and the slurry in each layer is deposited line by line to cover the entire layer; (4) The cemented carbide blank is subjected to vacuum sintering to obtain a micro-nano dual-scale structured cemented carbide.
2. The method for preparing micro-nano dual-scale cemented carbide according to claim 1, characterized in that: The micron-scale WC particle size is 0.8-5 μm; the nano-scale WC particle size is 0.1-0.5 μm.
3. The method for preparing micro-nano dual-scale cemented carbide according to claim 1, characterized in that: The bonding phase I and the bonding phase II are both Co powders, and the particle size of the Co powder is 0.6-1.0 μm.
4. The method for preparing micro-nano dual-scale cemented carbide according to claim 1, characterized in that: The ratio of micron-grade WC to bonding phase I is 70-94wt% for micron-grade WC and 6-30wt% for bonding phase I, and the sum of the two is 100%; the ratio of nano-grade WC to bonding phase II is 70-94wt% for nano-grade WC and 6-30wt% for bonding phase II, and the sum of the two is 100%.
5. The method for preparing micro-nano dual-scale cemented carbide according to claim 1, characterized in that: The wet grinding method in steps (1) and (2) is as follows: adding a molding agent at a ratio of 1-60% of the total weight of the ingredients, adding a wet grinding agent at a ratio of 1-60% of the total weight of the ingredients, the ball-to-material ratio is (6-12):1, the rotation speed is 50-500 r / min, and the time is 6-60 h.
6. The method for preparing micro-nano dual-scale cemented carbide according to claim 5, characterized in that: The molding agent is polyethylene glycol or paraffin, and the wet grinding agent is ethanol.
7. The method for preparing micro-nano dual-scale cemented carbide according to any one of claims 1 to 6, characterized in that: The three-dimensional model of the dual-scale structure in step (3) is that the micron phase and the nano phase are alternately distributed in each layer, and the corresponding layer-by-layer powder spreading method is: in each layer, the micron-scale WC mixed slurry and the nano-scale WC mixed slurry are alternately deposited to form alternatingly distributed micron-scale WC mixed slurry strips and nano-scale WC mixed slurry strips.
8. The method for preparing micro-nano dual-scale cemented carbide according to any one of claims 1 to 6, characterized in that: The three-dimensional model of the dual-scale structure in step (3) is a layer of micron phase and a layer of nano phase alternately distributed, and the corresponding layer-by-layer powder spreading method is: first deposit a layer of micron-scale WC mixed slurry, and then deposit a layer of nano-scale WC mixed slurry, and the micron-scale WC mixed slurry layer and the nano-scale WC mixed slurry layer are deposited alternately.
9. The method for preparing micro-nano dual-scale cemented carbide according to claim 1, characterized in that: The vacuum sintering conditions are: vacuum degree 10-2-10-4Pa, 300-800°C, heat preservation for 1-3h for degreasing, then continue to heat up to 1300-1500°C, and keep warm for 0.2-4h.
10. The micro-nano dual-scale cemented carbide prepared by the method according to any one of claims 1 to 9, characterized in that: It comprises 70-94wt% of hard phase micron-scale WC and nano-scale WC, and 6-30wt% of bonding phase; the mass ratio of the micron-scale WC and nano-scale WC is (3-7): (3-7).
Citation Information
Patent Citations
High-strength and high-conductivity Cu-Cr-Nb alloy with double-peak grain size and double-scale nano-phase reinforcing function
CN112391556A
Nanocrystalline hard alloy additive manufacturing method
CN117684035A